BETWEEN CARE AND OVERBURDEN: GENDER INEQUALITIES IN THE DIVISION OF LABOR IN PRIMARY HEALTH CARE - de Andrade Brandão, Miriam; Fabíola Silva Araújo, Mayonara; Moisés de Lima Júnior, Erivar; Ricardo de Lima Santos, Lauro; Túlio Araújo Gonçalves, Jonas; Ribeiro da Cunha Arruda, Vitória; Regina Raimundo de Souza, Barbara; Alexandre dos Santos, Ricardo; Mayara Galvão Rafael Medeiros, Fabrícia (Revista Gênero e Interdisciplinaridade, 2026)
Gender inequalities in the division of labor in healthcare represent a structural phenomenon that directly affects working conditions, professionals’ health, and the quality of care, particularly within Primary Health Care. This study aimed to analyze the relationship between care and overload from a gender perspective, highlighting its effects on women and on the organization of healthcare work. This is a theoretical-reflective study based on a critical analysis of scientific literature. The findings indicate that care, historically attributed to women, remains invisible and undervalued in both domestic and professional contexts, contributing to overload resulting from double or triple work shifts. This condition is associated with significant impacts on women’s physical and mental health, including stress, anxiety, and burnout, as well as impairing the quality of care provided. Additionally, these inequalities are intensified when intersecting with other social determinants, such as race and class, resulting in broader inequities. It is concluded that addressing these disparities requires structural changes, including the recognition of care as work, the redistribution of responsibilities, and the implementation of public policies aimed at promoting gender equity and improving working conditions in healthcare.